Differential effects of reduced mineralocorticoid receptor activation by unilateral adrenalectomy vs mineralocorticoid antagonist treatment in patients with primary aldosteronism - Implications for depression and anxiety. (May 2021) - Murck, Harald; Adolf, Christian; Schneider, Anna; Schlageter, Lena; Heinrich, Daniel; Ritzel, Katrin; Sturm, Lisa; Quinkler, Marcus; Beuschlein, Felix; Reincke, Martin; Künzel, Heike
Abstract: The mineralocorticoid receptor (MR) and its ligand aldosterone have been found to play a major role in the pathophysiology of depression. Both could be targets of therapeutic interventions. We analyzed laboratory data and questionnaires evaluating anxiety (using GAD-7 questionnaire) and depression (using PHQD questionnaire) of up to 210 patients with primary aldosteronism (PA) (82 females, 54.7 ± 12.0yrs; 128 males, 48.7 ± 12.8yrs) before and one year after initiation of specific treatment of PA by either adrenalectomy (ADX) or treatment with mineralocorticoid receptor antagonists (MRA). After ADX normalization of aldosterone excess was observed. This was associated with a significant reduction of depressive symptoms, but no significant change in GAD-7 score. MRA treatment was accompanied with persistent high aldosterone levels, but led to a significant improvement of anxiety, but no significant changes in PHQD scores. These data suggest different mechanistic pathways for depression and anxiety mediated via the MR. For treatment of depression a reduction of aldosterone levels might be relevant at CNS locations specific for aldosterone, whereas MRA targets MR more broadly, including areas, where cortisol is the main ligand. MRA may be useful in treatment of anxiety related behavior.